2020
DOI: 10.1097/md.0000000000022444
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of miRNA-146a to systemic lupus erythematosus

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
1
Order By: Relevance
“…So, exploring abnormal expression molecules of CD4+ T Journal of Immunology Research lymphocytes in SLE patients may provide reliable targets for the diagnosis, efficacy, and prognosis evaluation of SLE and is also crucial for inhibiting SLE apoptosis and alleviating related cellular dysfunction. Numerous studies have shown that the abnormal miRNA expression is involved in the nosogenesis of SLE [40,41]. Along with the development of miRNA panels, miRNAs have been a research hotspot in the diagnostic area, but the therapeutic market that is driven primarily by antagomiR and miRNA mimic products is underdeveloped.…”
Section: Discussionmentioning
confidence: 99%
“…So, exploring abnormal expression molecules of CD4+ T Journal of Immunology Research lymphocytes in SLE patients may provide reliable targets for the diagnosis, efficacy, and prognosis evaluation of SLE and is also crucial for inhibiting SLE apoptosis and alleviating related cellular dysfunction. Numerous studies have shown that the abnormal miRNA expression is involved in the nosogenesis of SLE [40,41]. Along with the development of miRNA panels, miRNAs have been a research hotspot in the diagnostic area, but the therapeutic market that is driven primarily by antagomiR and miRNA mimic products is underdeveloped.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, the study found a reverse correlation between type 1 interferon and SLE disease activity ( 14 ). In addition, recent meta-analyses showed that miR146a expression is associated with SLE risk and there were further differences in the expression of miR146a in Asian versus Caucasian populations ( 61 , 62 ). These differences in the expression level could be due to sample size, medications and active versus inactive disease status in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al confirmed the roles of miR‐371b‐5p and miR‐5100 in the serum of patients with SLE 10 . Fang and colleagues have reported the relationship between miR‐146a and SLE 11 . Furthermore, miR‐153‐3p has been reported to induce immune dysregulation by inhibiting PELI1 expression in patients with SLE, 12 which indicates that miR‐153‐3p may be a new therapeutic target for the treatment of LN.…”
Section: Introductionmentioning
confidence: 88%
“… 10 Fang and colleagues have reported the relationship between miR‐146a and SLE. 11 Furthermore, miR‐153‐3p has been reported to induce immune dysregulation by inhibiting PELI1 expression in patients with SLE, 12 which indicates that miR‐153‐3p may be a new therapeutic target for the treatment of LN. However, the roles and molecular mechanism of miR‐153‐3p in LN remain unclear.…”
Section: Introductionmentioning
confidence: 99%